Consciousness, intentionality and intercorporeality - Coelho Junior, Nelson Ernesto (Paidéia (Ribeirão Preto), 2002)
The aim of this paper is to situate and discuss consciousness, intentionality and intersubjectivity in Edmund Husserl's and Maurice Merleau-Ponty's phenomenological theories, in the context of a debate about Arno Engelmann's Theory of the Two Consciousness. Three questions are proposed to professor Arno Engelmann.